STUDENTS ATTITUDE IN LEARNING ENGLISH CONVERSATIONS - Sury . Utami; Rahmad . Husein; Zainuddin . Zainuddin (LINGUISTIK TERAPAN, 2022)
English conversation is an important lesson for Senior High School students in order to face the globalization effects. Many students considered English conversation as a controversial lesson through their positive and negative attitudes toward it. This study aimed to investigate the types of attitudes of the Senior High School students in learning English conversation, to describe the realization of the attitudes of Senior High School students in learning English conversations, and to explain the reason of the attitude which Senior High School students realized in the ways they are. The subjects of this study were 20 students consisting 12 females and 8 males at the age of 16-18 years old. The data were collected by observations and interviews then were analyzed using Interactive Models. The result showed that positive and negative attitude in learning English conversations, five types of realizations, and the reasons of the students realized their attitudes i.e. the language loyalty, language pride,  and awareness of language norms. It was concluded that the students’ attitude varied as to positive and negative ones and realized in numerous manners affected by several factors. Keywords: Discourse Markers, Students Interactions, Nonformal Education, Conversation